Maksimasi Keuntungan Produksi Kue Menggunakan Pendekatan Turunan - Zul Ammar (MANABIS: Jurnal Manajemen dan Bisnis, 2024)
Based on observations at one of the cake production businesses, namely the Nora Cake Shop, the owner complained that the profits from PIA-PIA Cake production were not maximized. This research aims to analyze the maximum profit obtained by a business by applying the concept of derivatives. This research is quantitative research using the case study method. The research sample is data regarding the cake production and sales process. The research results show that maximum profit is analyzed using a derivative concept, through the steps: 1) Determine the Cost Function, Demand, Revenue, and Profit Function; 2) Determine the first derivative of the profit function; 3) Determine the critical point of the first derivative of the profit function; 4) Analyze the critical point using the second derivative. Based on the analysis results, sales will reach a maximum if PIA-PIA Cake sales are 1283 packs per month. Sales in the previous month according to the data obtained had not reached maximum results because the number of sales per month was still below the maximum sales value. Therefore, to obtain maximum profits the owner can increase production.